ETNOBOTANI PEWARNA ALAM TENUN IKAT DI DUSUN TEKALONG DESA LANJAK DERAS KABUPATEN KAPUAS HULU - Lolyta Sisillia; Anggelia Eni (Tengkawang : Jurnal Ilmu Kehutanan, 2019)
The study aims to obtain information about traditional knowledge and local wisdom of the Tekalong sub-village, Lanjak Deras Village, Kapuas Hulu Regency towards natural coloring plants and identify natural color plants dyes for weaving. The method of this study was participatory observation. Respondents was determined by using purposive sampling techniques. Plant Identification based on morphological characteristic, while local knowledge of the community is described based on the result of interviews with weaving craftsman in the Tekalong sub-village. The results showed that were 13 species of natural coloring plants found and utilized, namely Melastoma polyanthum BI, Albizia procera (Roxb.) Benth, Psychotria viridiflora (Reinw). Ex. Blume, Eusideroxylon zwageri Teijsm. & Binn, Shorea spp, Morinda citrifolia L., Garcinia mangostana L., Areca catechu L, Mangifera indica L., Cocos nucifera L., Nephelium lappaceum L., Durio zubethinus Murr, dan Artocarpus heterophyllus Lamk. Plant organs utilized are leaves, fruits, flowers, stems, roots and barks. The plant processing that are generally done by boiling and pounding. Color produced are purple, green, yellow, maroon, red and brown. The processing of natural dyes by the community of Tekalong sub-village still pays attention on their customs and prohibitions or restrictions in their culture.Keywords: Ethnobotany, identification, indigenous knowledge, natural color